Self-Medication Practices Among Population in the Sulaimani City, Kurdistan Region, Iraq - Soran Hamalaw (Al-Anbar Medical Journal)
Background: Self-medication is a prevalent practice worldwide, playing a vital role in managing minor ailments and symptoms, particularly in regions with limited healthcare access. However, prevalence, impact, and justifications for self-medication are varied across communities.Objectives: To evaluate the prevalence and identify determinant factors related to self-medication practices among the residents of Sulaimani city in the Kurdistan region of Iraq.Methods: A descriptive cross-sectional study was conducted in Sulaimani City from November 2022 to March 2023. All adults (≥ 18 years) were eligible for this study. The data was collected from different zones of the city via the convenience sampling method. A structured questionnaire was prepared and applied via face-to-face interviews, which took place in large malls and door-to-door approaching individuals in residential neighbourhoods, and recruiting participants, for data collection.Results: The survey involved 500 participants; the self-medication prevalence was 73.4%. The age, educational level, and occupation of the participants were factored into the practice of self-medication (P-value = 0.001). Pharmacists were the main providers of information on self-medication (54.5%) and primary sources of medications (92.9%). The primary reason for self-medication was participants' perception that their illness was not severe (65.4%). Headache was the most common ailment (64.6%), followed by the common cold and flu (57.2%). Analgesics were the most frequently used drugs (82.3%). The majority of self-medicated individuals (71.9%) did not report experiencing any adverse effects from self-medication.Conclusions: Self-medication was highly prevalent in Sulaimani City, primarily for minor ailments, with headaches being the most common reason. Pharmacies are crucial for information and drug procurement. Even though, the study suggests that while self-medicated individuals are unlikely to experience adverse effects from their drugs, promoting rational drug use is recommended to mitigate its negative consequences.